Predictive role of atrial fibrillation in cognitive decline: a systematic review and meta-analysis of 2.8 million individuals . Issue 8 (21st January 2022) - Koh, Yu Han; Lew, Leslie Z W; Franke, Kyle B; Elliott, Adrian D; Lau, Dennis H; Thiyagarajah, Anand; Linz, Dominik; Arstall, Margaret; Tully, Phillip J; Baune, Bernhard T; Munawar, Dian A; Mahajan, Rajiv
Abstract: Aims: To systematic review and meta-analyse the association and mechanistic links between atrial fibrillation (AF) and cognitive impairment. Methods and results: PubMed, EMBASE, and Cochrane Library were searched up to 27 March 2021 and yielded 4534 citations. After exclusions, 61 were analysed; 15 and 6 studies reported on the association of AF and cognitive impairment in the general population and post-stroke cohorts, respectively. Thirty-six studies reported on the neuro-pathological changes in patients with AF; of those, 13 reported on silent cerebral infarction (SCI) and 11 reported on cerebral microbleeds (CMB). Atrial fibrillation was associated with 39% increased risk of cognitive impairment in the general population [ n = 15: 2 822 974 patients; hazard ratio = 1.39; 95% confidence interval (CI) 1.25–1.53, I 2 = 90.3%; follow-up 3.8–25 years]. In the post-stroke cohort, AF was associated with a 2.70-fold increased risk of cognitive impairment [adjusted odds ratio (OR) 2.70; 95% CI 1.66–3.74, I 2 = 0.0%; follow-up 0.25–3.78 years]. Atrial fibrillation was associated with cerebral small vessel disease, such as white matter hyperintensities and CMB ( n = 8: 3698 patients; OR = 1.38; 95% CI 1.11–1.73, I 2 = 0.0%), SCI ( n = 13: 6188 patients; OR = 2.11; 95% CI 1.58–2.64, I 2 = 0%), and decreased cerebral perfusion and cerebral volume even in the absence of clinical stroke. Conclusion: Atrial fibrillation is associated with increased risk of cognitive impairment. The association with cerebral small vessel disease and cerebral atrophy secondary to cardioembolism and cerebral hypoperfusion may suggest a plausible link in the absence of clinical stroke. PROSPERO CRD42018109185. Graphical Abstract: